Pengaruh Model Pembelajaran Kooperatif Tipe Two Stay Two Stray Terhadap Hasil Belajar IPAS Siswa Kelas V SDN Tengah 03 - Julyani, Tri Nadia; Kasriman, Kasriman (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to determine the effect of the Two Stay Two Stray type cooperative learning model on the learning outcomes of fifth grade students of SDN Tengah 03. This research uses a quantitative approach with a pseudo-experimental design type of nonequivalent control group design. The sample consisted of two classes, each consisting of 30 students, namely the experimental class and the control class. Data collection was carried out through pretest and posttest in the form of 10 essay questions to measure student learning outcomes in IPAS subjects. Data analysis was carried out through normality, homogeneity, and hypothesis testing with Independent Sample T-Test. The results of the analysis showed that the average value of the experimental class posttest (84.33) was higher than the control class (58.83). Hypothesis testing showed a significance value of <0.001, which indicates a significant difference between groups. This study concludes that the Two Stay Two Stray model significantly improves learning outcomes, creates an active and collaborative atmosphere, and has a real impact on student academic achievement at SDN Tengah 03. The findings recommend the application of this model by teachers to create fun and effective learning.